2018
DOI: 10.3389/fimmu.2017.01928
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Split Vaccines Confer Partial Cross-Protection against Heterologous Influenza Virus in Ferrets When Combined with the CAF01 Adjuvant

Abstract: Influenza epidemics occur annually, and estimated 5–10% of the adult population and 20–30% of children will become ill from influenza infection. Seasonal vaccines primarily work through the induction of neutralizing antibodies against the principal surface antigen hemagglutinin (HA). This important role of HA-specific antibodies explains why previous pandemics have emerged when new HAs have appeared in circulating human viruses. It has long been recognized that influenza virus-specific CD4(+) T cells are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
(27 reference statements)
3
15
0
Order By: Relevance
“…Furthermore, the Addavax + NG-34 group did not boost Th1 and Th2 as demonstrated in other studies [25,26]. In contrast, our results were concordant with results using CAF01 combined with TIV, which conferred protection in an IHAindependent manner [29].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the Addavax + NG-34 group did not boost Th1 and Th2 as demonstrated in other studies [25,26]. In contrast, our results were concordant with results using CAF01 combined with TIV, which conferred protection in an IHAindependent manner [29].…”
Section: Discussionsupporting
confidence: 91%
“…Another report indicated that cationic adjuvant formulation (CAF)01-adjuvanted TIV protected not only against homologous but also against heterologous IAV infection despite the absence of neutralization based on HI (34). CAF01 is a newly developed liposomal adjuvant which is based on liposomes formed by N,N′-dimethyl-N,N′-dioctadecylammonium with Fig.…”
Section: Discussionmentioning
confidence: 99%
“…the synthetic mycobacterial immunomodulator α,α′-trehalose 6,6′-dibehenate inserted into the lipid bilayers. In the study, Christensen et al (34) concluded that CAF01-adjuvanted TIV vaccine can reduce virus shedding and systemic disease symptoms, but does not reduce local inflammation in the nasal cavity. Although the subclass of HA-specific IgGs was not assessed in the study as experiments were primarily conducted in ferrets, we speculated that there were indeed differences in isotype switching for HA-specific IgGs when compared to vaccination with the conventional TIV alone, because CAF01 is known to induce T h 1/T h 17-type T-cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…CAF01 was also able to stimulate humoral immune responses. Trivalent influenza split-virion (TIV) vaccine was co-administered with CAF01 into ferrets [ 175 ]. The TIV-CAF01-vaccinated ferrets produced significantly higher influenza-specific IgG antibody titers than non-adjuvanted vaccine candidates.…”
Section: Carbohydrate-based Adjuvantsmentioning
confidence: 99%